Formation of a bioactive cyclopentenone and its adducts with amino acids in sterilized-fruits and - vegetables baby foods. (1st June 2022) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Fernández-Prior, África; Rodríguez-Juan, Elisa; Fernández-Bolaños, Juan
Graphical abstract: Highlights: Cyclopentenone was formed in sterilized vegetable- and fruit-based baby food. Cyclopentenone (DHCP) showed high reactivity with selected amino acids. DHCP forms covalent adducts with cysteine, histidine and glutathione. Identification of DHCP in heat-treated foods is difficult due to the adducts. Abstract: The formation of the molecule 4, 5-dihydroxy-2-cyclopenten-1-one (DHCP) from the thermal treatment of pectin-containing foods was investigated in small-scale laboratory preparation of sterilized vegetable puree (carrot, zucchini and tomato) and fruit puree (peach and mixture of pear and apple) and in commercial baby foods. DHCP attracts attention due to its cytotoxicity as well as potential antiviral and anti-inflammatory effects. However, its effects and the difficulty of its identification in food are mediated in part by the formation of Michael adducts of DHCP with amino acids. The results revealed that DHCP reacted efficiently with cysteine and glutathione, and to a lesser extent with histidine. Mass spectrometry analysis confirmed the formation of adducts of DHCP with amino acids in a model system, being in a real food system difficult to investigate. However, these formed adducts are of potential interest, although it is not known whether they are safe, bioactive or reversible.